Innovative alternatives in the surgical management of glaucoma with cataract surgery. (3rd September 2017) - Ianchulev, Tsontcho; Ahmed, Iqbal I. K.; Stamper, Robert L.; Chang, David F.; Samuelson, Thomas W.; Lindstrom, Richard L.
ABSTRACT: Introduction : Glaucoma is the leading cause of irremediable blindness worldwide. The prevalence of glaucoma will continue to increase with the increased ageing of the global population. The only way to reduce the progression of vision loss due to glaucoma is to control the level of intraocular pressure (IOP). IOP control initially depends upon pharmaceutical interventions. The efficacy of IOP-lowering medications is limited by poor patient compliance, incorrect medication administration, ocular side effects and cost. When IOP-lowering medications fail to halt the progression of glaucoma, surgical intervention, such as trabeculectomy or glaucoma drainage device surgery, is indicated, but neither has been found completely satisfactory. Surgical interventions have a significant risk of complications that result in decreased vision. Areas covered: This article summarizes the design and function, as well as reviewing the efficacy, of various innovative, highly safe, surgical approaches to the treatment of glaucoma. Expert opinion: Recent treatment innovations have taken advantage of the fact that many patients with mild-to-moderate glaucoma also have cataracts. Devices and procedures have been developed that are no more invasive than cataract surgery and that can be performed concurrently with cataract surgery. These IOP-lowering treatments have an excellent safety profile and minimize ocular tissue trauma.